High Strength and High Modulus Electrospun Nanofibers - Jian Yao; Cees W. M. Bastiaansen; Ton Peijs (Fibers, 2014)
Electrospinning is a rapidly growing polymer processing technology as it provides a viable and simple method to create ultra-fine continuous fibers. This paper presents an in-depth review of the mechanical properties of electrospun fibers and particularly focuses on methodologies to generate high strength and high modulus nanofibers. As such, it aims to provide some guidance to future research activities in the area of high performance electrospun fibers.